2015
DOI: 10.1515/amm-2015-0164
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure And Mechanical Properties Of Al-WC Composites

Abstract: The scope of the research work is the production and characterization of Al matrix composites reinforced with WC ceramic nanoparticles. The synthesis process was powder metallurgy. The produced composites were examined as far as their microstructure and mechanical properties (resistance to wear, micro/macrohardness). Intermetallic phases (Al 12 W and Al 2 Cu) were identified in the microstrucutre. Al 4 C 3 was not detected in the composites. Adding more than 5 wt% WC to the aluminum, microhardness and wear res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
(14 reference statements)
4
10
0
Order By: Relevance
“…The microstructure of the Al-WC composite comprises the Al matrix with a new greyish phase, larger than the primary WC particle size, and non-reacted WC particles (Figure 9b). The phase formed is indicated as Al 12 W, according to stoichiometry obtained by electron dispersive spectroscopy analysis, and it is consistent with other studies [44,45]. Thus, the hardening effect in Al-WC can be caused by three occurrences: The grain size refinement, phase transformation, and the non-reacted dispersed WC particles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The microstructure of the Al-WC composite comprises the Al matrix with a new greyish phase, larger than the primary WC particle size, and non-reacted WC particles (Figure 9b). The phase formed is indicated as Al 12 W, according to stoichiometry obtained by electron dispersive spectroscopy analysis, and it is consistent with other studies [44,45]. Thus, the hardening effect in Al-WC can be caused by three occurrences: The grain size refinement, phase transformation, and the non-reacted dispersed WC particles.…”
Section: Discussionsupporting
confidence: 89%
“…Related studies reported the strengthening effect of the WC in the Al matrix through other PM approaches, e.g., ball milling, it being reported that the hardness increases with the increase in both the milling time and the WC content [44];~23% increase in the hardness obtained by 15 wt. % WC, with a reverse effectiveness caused by increasing the milling time [45]; a hardness increase of 40% by 10 wt. % WC [46]; or an incremental hardness growth resulting from increasing the amount of WC with an opposite effect on tensile strength and densification [47].…”
Section: Discussionmentioning
confidence: 99%
“…These maps confirm the formation of a new phase, consisting of Al and W, formed during sintering and dispersed in the matrix of Al. This phase is probably Al12W, according to the stoichiometry obtained by EDS analysis, which is consistent with other studies [5,13]. The C resulting from this reaction appears to be in the crystal lattice of this new phase or formed as Al4C3 at the interface which has not been detected by SEM techniques, thus further evaluations will be .…”
Section: Microstructural Characterization Of the Al-1 Vol% Wc Compositesupporting
confidence: 91%
“…Moreover, just a small amount of heavy refractory powder as a reinforcement is enough to lead to notable mechanical property improvements [12]. Fabrication of AMCs reinforced by WC micro-particles by powder metallurgy and casting methods is currently receiving a growing research attention owing to a significant improvement of mechanical properties (at the expense, however, of ductility [13]) and increase in the wear resist-ance [14,15]. (b2) Application of mechanical stirring that can support the favorable wetting characteristics of less than 90° contact angle and provide the necessary shear forces for total particle insertion [16].…”
Section: Introductionmentioning
confidence: 99%